Global Experience Industries : the Business of Experience Economy. - Christensen, Jens (Aarhus University Press, 2009)
The experience economy is a fourth economic field, different from commodities, goods and services. Experiences are an economic value that is added to a product or identical with a product. When you buy an experience, you pay to spend time enjoying a series of memorable events that a company stages to engage a customer in a personal way. Fueled by an expanding global and digital economy, the experience dimension has moved into a predominant place since the 1990s. In developed countries, people have become richer and more individualized, and with all their basic material needs being met they focu.